MONEY CONTESTATION: PROSTITUTION SNARE SPG (SALES PROMOTION GIRL) IN INDAH HANACO’S THE CURSE OF BEAUTY NOVEL - Fiqih Aisyatul Farokhah (Aksara, 2019)
In this globalization era, with the high technology money becomes the important thing in human life. Sometimes, it is synchronous to the values and morals. Even, they have a good educational background, it is not guaranteed. Many women are one of the victims of underdevelopment society. The lacking of learning opportunity makes them should survive in a difficult life. Finally, the only thing they can do is using their body to work. Money, family, and social environment have the role important in individual deviation. One of them is women who work as Sales Promotion Girl (SPG). They are taken into the prostitution. This reality is represented in Indah Hanaco’s novel “The Curse of Beauty”. Thus, this paper reveals the representation of women sexuality in her novel. It explains their underdevelopment education and sexual oppression. Therefore, there are some research problems to be discussed. First, what does mean money contestation of SPG’s life?. Then, how does the education affect SPG’s life in The Curse of Beauty novel?. Next, how do money and education affect SPG in the prostitution world?. This paper aims to open up the money contestation affect the SPG’s life until they are trapped in the prostitution world. It uses descriptive qualitative. Data are taken from all descriptive concerning SPG body appearance to understand the narrative meaning of the beauty. It applies power and subject theory of Michael Foucault. Money and education have changed women life to the sexual oppression which brings them to the prostitution world.